(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article provides a scientific analysis of the role of modern educational technologies in developing academic writing skills among students, the pedagogical effectiveness of digital tools, and the automation of text generation processes.